2009
DOI: 10.1016/j.jmathb.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prospective elementary teachers use of representation to reason algebraically

Abstract: a b s t r a c tWe used a teaching experiment to evaluate the preparation of preservice teachers to teach early algebra concepts in the elementary school with the goal of improving their ability to generalize and justify algebraic rules when using pattern-finding tasks. Nearly all of the elementary preservice teachers generalized explicit rules using symbolic notation but had trouble with justifications early in the experiment. The use of isomorphic tasks promoted their ability to justify their generalizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 25 publications
2
25
0
1
Order By: Relevance
“…Teacher observations and informal assessment techniques can be used in conjunction with the list of indicators generated in Table . In effect, this list is another method for teachers to assist students' progress toward understanding multiplication and in determining the trajectories of students' multiplicative reasoning so that teachers can remediate and develop steps toward additional understanding (Ball, ; Richardson et al., ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher observations and informal assessment techniques can be used in conjunction with the list of indicators generated in Table . In effect, this list is another method for teachers to assist students' progress toward understanding multiplication and in determining the trajectories of students' multiplicative reasoning so that teachers can remediate and develop steps toward additional understanding (Ball, ; Richardson et al., ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Advanced mathematical thinking is viewed as beginning in elementary school with multiplicative reasoning (Clark & Kamii, ; Harel & Sowder, ; Piaget, ). Richardson, Berenson, and Staley () in addition to Ball () acknowledge the requirement for additional research concerning preservice as well as in‐service teachers' understanding of multiplicative reasoning.…”
Section: Background Literaturementioning
confidence: 99%
“…The problem solving strategy among pupils is different, this is influenced by the learning style that each pupil has [8]. Learning styles are a complex way in which pupils perceive and feel most effective and efficient in processing, storing, and recalling what they have learned [9]. Learning styles are classified into 3 types; visual, auditory, and kinesthetic [10].…”
Section: Introductionmentioning
confidence: 99%
“…Radford (1996) argued that "the logical base underlying generalization is that of justifying the conclusion" (p. 111). Unfortunately, few researchers have studied how pre-service teachers' knowledge of generalization and justification are associated (e.g., Richardson, Berenson, & Staley, 2009). This study seeks to gain an understanding of each construct and the interaction between them within the context of quadratic relationships.…”
Section: Justificationmentioning
confidence: 99%
“…The researchers observed that some participants justified their rule by aligning their rules to figures presented in the task, whereas other participants aligned their rules to numerical values from the task to argue the appropriateness of their rule. Another example can be seen in the work of Richardson et al (2009) where the researchers studied elementary preservice teachers' ability to justify their rules to linear geometric-numerical patterning tasks. The researchers found that in the beginning of the study the preservice teachers had difficulty justifying their developed rules, often being able to start their justifications, but unable to complete them.…”
Section: Justification As Associated With Inductive Reasoningmentioning
confidence: 99%